Use of an Accessible iPad App and Supplemental Graphics to Build Mathematics Skills: Feasibility Study Results. (September 2015) - Beal, Carole R.; Rosenblum, L. Penny
Introduction: The present study evaluated the feasibility of using an iPad application or "app" for algebra-readiness mathematics, with accompanying braille materials and accessible graphics, when used in authentic educational settings. Methods: Twenty-nine students with visual impairments in grades 4–11 used the materials under the direction of their teachers of students with visual impairments ( N = 19). Twenty percent of the mathematics problems included graphics such as maps, line graphs, and bar graphs. Students and teachers of students with visual impairments provided feedback about the feasibility of using the app with supplemental materials, and made suggestions for additional features to improve the instructional package. Results: Students completed 984 word problems and solved 80% of them correctly within three attempts. The use of some features such as hints and "worked-example" videos was low. Participants provided suggestions for improvement of the app features and accessible graphics. Discussion: Students and teachers of students with visual impairments were able to use the materials successfully, and comments were generally positive. Participants' comments and suggestions were used to revise the app and materials. Implications for practitioners: The study results contribute to the growing body of knowledge about the potential value of tablet-type devices for use by visually impaired students.